PROTOCOLS FOR OND (Short Rains) 2023 Growing Season - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A protocol was developed to establish AICCRA's on-farm demonstration plots for the short rains season of October-November-December 2023 in Makueni, Kitui and Taita Taveta Counties. This protocol outlines the specific roles and responsibilities of extension officers and lead farmers, covering various activities from land preparation to harvesting. It employs a randomized block design, integrating conservation agriculture and conventional tillage systems, with both sole cropping and intercropping of legumes and cereals. The protocol underscores the importance of data collection, including rainfall measurements and documentation of on-farm operations by lead farmers, to facilitate effective evaluation of yield metrics. Moreover, it incorporates provisions for farmer evaluations, a seasonal calendar, and field visit checklists, ensuring a systematic and collaborative approach throughout the process.